1973
DOI: 10.1007/bf00153449
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind density model from km-wave type III bursts

Abstract: The analysis of type III bursts observed from the OGO-5 satellite between 3.5 MHz and 50 kHz (46 km) gives an empirical expression for the frequency drift rate as a function of frequency that is valid from 75 kHz to 550 MHz. Using this expression and some simplifying assumptions we obtain indirectly an empirical formula for the electron density distribution of the solar wind to 1 AU which is consistent with published values of electron density and with observed type II1 burst drift rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
96
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 15 publications
17
96
0
Order By: Relevance
“…The burst drifts down in frequency due to the beam propagation into low-density regions. Using the approach by Alvarez & Haddock (1973) 2. The radio flux and its variation with frequency are consistent with observations (e.g., Wild et al 1954;Suzuki & Dulk 1985).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The burst drifts down in frequency due to the beam propagation into low-density regions. Using the approach by Alvarez & Haddock (1973) 2. The radio flux and its variation with frequency are consistent with observations (e.g., Wild et al 1954;Suzuki & Dulk 1985).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Direct analyses of in situ D ensity measurements within the radio burst source location and a thorough understanding of the influence of scattering in the interplanetary medium art certainly needed before the interplanetary radio burst methods can be very accurately used as a common tool to remotely determine the solar wind density. For instance density models 7: Fainberg and Stone (1971) 8: Alvarez and Haddock (1973): the model shown on this Figure is normalized to the 1 AU Helios density found in this paper (6.14 cm -3 .) 9: Bougeret et al (1982) 10: The Helios density model found in this paper.…”
Section: The Density Falloffmentioning
confidence: 97%
“…Following Alvarez and Haddock (1973), we shall use the following i expression for the density: N(r) = A (r-b) P (1).…”
Section: Introductionmentioning
confidence: 99%
“…Alvarez and Haddock [1973] also calculated these parameters for type IIIs and obtained similar coefficients to those of the LOFAR Type III fit: a = 10.9 × 10 −3 ± 1.1 × 10 −3 and b = 1.84 ± 0.02. The parameters for the type III fit are very close in magnitude to those of the LOFAR S bursts fit suggesting that a similar mechanism is generating these bursts.…”
Section: Resultsmentioning
confidence: 67%